2021
DOI: 10.1371/journal.pone.0250908
|View full text |Cite
|
Sign up to set email alerts
|

How did beliefs and perceptions about e-cigarettes change after national news coverage of the EVALI outbreak?

Abstract: Introduction Exposure to media content can shape public opinions about tobacco. In early September 2019, the outbreak of e-cigarette, or vaping, product use–associated lung injury (EVALI) became headline news in the United States. Methods In August and September 2019, we conducted two cross-sectional online surveys with current and former smokers assessing attitudes and beliefs about e-cigarettes. Study one (n = 865) was collected before the EVALI outbreak was widely covered and study two (n = 344) was colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Studies in the USA and elsewhere have documented increases in e-cigarette harm perceptions after the EVALI outbreak 9–14. However, limited research has focused on knowledge of EVALI itself or EVALI’s impact on smokers’ e-cigarette perceptions and intentions.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the USA and elsewhere have documented increases in e-cigarette harm perceptions after the EVALI outbreak 9–14. However, limited research has focused on knowledge of EVALI itself or EVALI’s impact on smokers’ e-cigarette perceptions and intentions.…”
Section: Introductionmentioning
confidence: 99%
“…8 Although the injuries are now thought to largely be associated with the use of vitamin E acetate as a diluent for tetrahydrocannabinol (THC) containing liquids, early CDC reports suggested nicotine vaping as the cause. 8,34 The consequent emphasis on dangers of vaping in US news resulted in more negative public perceptions of ENDS use and more of the public discourse focusing on their potential dangers to youth, [35][36][37][38][39] in contrast to countries like the UK, where there has been more emphasis on ENDS' potential benefits for adults. 40,41 Additionally, in the US, many states and localities enacted restrictions or bans on flavored ENDS sales in 2020 and 2021.…”
Section: Discussionmentioning
confidence: 99%
“… 59 , 60 Studies have shown increased news coverage to impact public perceptions on health behaviors, like changes in harm perceptions related to e-cigarette use. 61 Recent research is indicating that reporting of health policy has been framed to focus on politics and partisanship instead of policies or their potential impacts. For example, a study on news coverage of the Affordable Care Act (ACA) found that the most common sources of news provided little public-health-relevant substance about the ACA even after its implementation.…”
Section: Discussionmentioning
confidence: 99%